Embedded systems: architecture, programming and design - Kamal, Raj (Tata McGraw-Hill, 2008)
Embedded systems: architecture, programming and design / Kamal, Raj. -- New Delhi: Tata McGraw-Hill, 2008 005.1 K15e2 2nd ed. No. of Copies : 1